Innovating under pressure: Adopting digital technologies in social care organizations during the COVID-19 crisis. (July 2022) - Kateb, Sanaz; Ruehle, Rebecca C.; Kroon, David P.; van Burg, Elco; Huber, Max
Abstract: To provide ongoing support for vulnerable groups during the COVID-19 pandemic, social care organizations had to shift abruptly to e-health solutions. Qualitative data from three cases illustrate that, more than a year into the pandemic, those adoptions of digital technologies developed differently; the current study aims to shed light on the processes that lead to such differences. Notably, the first organization resisted the large-scale use of digital technologies; the second faced intra-organizational disagreement about the role of digital technology for care provision; and the third organization struggled but managed a broader, more successful adoption of digital technology. The multiple case study findings contribute to extant literature, by (1) detailing the digital innovation process, focusing on the crucial adoption process for digital technology; (2) demonstrating that champions and a shared vision can both enable and constrain the adoption of digital technologies in crisis situations; (3) emphasizing the importance of individual members' professional identities for determining adoption of digital technologies; and (4) reflecting on the conscious use of transformation practices, even in the ad hoc setting of adopting digital technology during a crisis. Highlights: -Social care organizations had to turn abruptly towards e-health due to Covid-19. -Digital technologies were adopted differently, between resistance and acceptance. -Champions and a shared vision not only enable but can also constrain adoption. -It is important that digital technology is connected to professionals' identity. -To address adhocness, conscious use of transformation practices is important.